ALAT PANDETEKSI MANUSIA PADA AREA GEDUNG BERBASIS MIKROKONTROLER MENGGUNAKAN SENSOR - Narado, Jefli Randy; Nopriadi, Nopriadi (Computer Science and Industrial Engineering, 2022)
The very rapid and comprehensive development of technology can no longer be denied and avoid its impact on our daily lives, be it in work, activity, communication and so on. Technology itself has the meaning of a whole means to provide the necessary goods for the survival and comfort of human life. One of them is technology that uses sensors in helping work such as human detection sensors in building areas. This final project aims to create a human detection tool in the building area based on sensors consisting of hardware such as Passive Infra Red (PIR) Sensors and Ultrasonic Sensors HC-SR04 as inputs, Arduino Uno and Atmega328 Microcontrollers as processors and Buzzers, LEDs, and Laptop Screens as outputs using the C / C + + program language (software) on the Arduino Integrated Development Environment (IDE) with a sketch that has been compiled into in the Arduino Uno board by using Atmega328. Arduino Uno is equipped with the Atmega328 microcontroller as a hardware control center on the human detection device so that it runs automatically. This human detection tool uses a testing method by directly testing the physical tool by placing the tool in a predetermined area of the building. The way this tool works is to focus on humans / other objects around the building area. The tool will work by capturing the presence of movement or humans through PIR sensors and Ultrasonic sensors. Which will then be processed through Arduino Uno which is equipped with an Atmega328 microcontroller which then outputs in the form of sms notifications, sounds on the Buzer, LEDs and movement radar on the laptop screen. Based on the results of the research that has been carried out, the human detection tool that has been designed by the researcher can work and operate in accordance with the established concept.